2020
DOI: 10.1021/acsomega.0c04096
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Periodic Wave Function Approach for the Study of Infinitely Periodic Solid-State Systems: II. Application to Helical Polysaccharides

Abstract: The cyclic periodic wave function (CPWF) approach is applied at the AM1 and PM3 semiempirical levels of approximation to two infinitely periodic polymer systems in the solid state. The two polysaccharides of interest here are (1→3)-β- d -glucan and (1→3)-β- d -xylan. Our calculated results show excellent agreement with the available data for the two polysaccharides and demonstrate that the use of the CPWF approach at the AM1 and PM3 levels of approximation provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Longer-range interactions are at least partially recovered by the use of our Madelung correction scheme, which corrects both the individual Fock matrix elements as well as the total energy by approximately recovering all interactions between farther neighbors . We have found that using N = 4 suffices for most solid-state systems, , as long as the intermonomer interactions are weaker than covalent interactions. Even when covalent interactions occur between monomers, we have found that N = 4 often suffices, though using N = 6 in the direction of the covalent interaction will provide greater accuracy for some systems.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Longer-range interactions are at least partially recovered by the use of our Madelung correction scheme, which corrects both the individual Fock matrix elements as well as the total energy by approximately recovering all interactions between farther neighbors . We have found that using N = 4 suffices for most solid-state systems, , as long as the intermonomer interactions are weaker than covalent interactions. Even when covalent interactions occur between monomers, we have found that N = 4 often suffices, though using N = 6 in the direction of the covalent interaction will provide greater accuracy for some systems.…”
Section: Discussionmentioning
confidence: 97%
“…Second, it is a chemically intuitive approach. The repeat units are chosen to be either the individual molecules within molecular solids or the individual monomer units within polymers, , and are placed at their exact translationally periodic positions, as found in the infinitely periodic crystal, without any built-in periodic boundary conditions (PBCs). For chemists, it is a more intuitive way to study large organic crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations